2010
DOI: 10.1208/s12248-010-9235-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Cutaneous Microdialysis Cytokine Findings Supported by End Point Biopsy Immunohistochemistry Findings?

Abstract: Abstract. Insertion of a cutaneous microdialysis catheter into normal dermis has been shown to induce the production of IL1b, IL6 and IL8 in an innate response to minimal trauma. In the present study, skin biopsy for immunohistochemistry has been performed at the site of the microdialysis catheter to compare the findings with that of the microdialysis findings 24 h after insertion. Of the three named cytokines, concordance between the two investigated technologies was highest for IL8 (100%) followed by IL6 (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Previously, 'end point biopsy' and MD have been combined in an attempt to relate levels of cytokines in microdialysate to actual presence of cytokines in the tissue [27]. Whilst "end point biopsy" is achievable, membranes are available in all MD experimental settings and can thus more conveniently fill an "information gap" than the more cumbersome performance of tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, 'end point biopsy' and MD have been combined in an attempt to relate levels of cytokines in microdialysate to actual presence of cytokines in the tissue [27]. Whilst "end point biopsy" is achievable, membranes are available in all MD experimental settings and can thus more conveniently fill an "information gap" than the more cumbersome performance of tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of the catheters followed the technique previously described in Ref. [27]. The point of insertion of each catheter was anaesthetized with 0.2 ml Xylocaine (10 mg/ml).…”
Section: Microdialysis In Forearm Skinmentioning
confidence: 99%
“…In the first 2 h, presence of cytokines in the microdialysate should imply presence of cytokines in the tissue, prior to induction of cytokines caused by the catheter insertion itself. The second period (3-8 h) can be interpreted as illustrating the response of the tissue (release of cytokines) to the insertion manoeuvre, which we view as a manifestation of innate skin reactivity to the minimal wound which the catheter insertion constitutes (20,32,42). The third period in the pre-equilibration phase (9 to 17 h period) is a recovery phase in which values move towards baseline.…”
Section: Resultsmentioning
confidence: 99%
“…For cytokines and other biologically active molecules, this period will be longer since local reactive changes meld into repair (20,31). The findings of the pre-equilibration period may be a "bonus" reflecting individual variability/phenotype in regard to innate reactivity to the "non-microbial/sterile" trauma which the catheter insertion constitutes (20,32). We view, however, the cytokine response after microdialysis catheter insertion as a manifestation of innate reactivity similar to the "sterile inflammation" of basic research models (26,33).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in psoriasis have shown microdialysis sensitive to dermal changes in mediator levels with minimal perturbations in corresponding plasma levels (109,110). Sjögren & Anderson compared cytokine findings in the skin by microdialysis and biopsies and found moderate to excellent agreement (138). Still, methodology studies may well be required to improve the translational value of microdialysis.…”
Section: Cystic Fibrosismentioning
confidence: 99%